High-density linkage map construction in an autotetraploid blueberry population and detection of quantitative trait loci for anthocyanin content - Montanari, Sara; Thomson, Susan; Cordiner, Sarah; Günther, Catrin S.; Miller, Poppy; Deng, Cecilia H.; McGhie, Tony; Knäbel, Mareike; Foster, Toshi; Turner, Janice; Chagné, David; Espley, Richard (Frontiers in Plant Science, 2022)
Highbush blueberry (Vaccinium corymbosum, 2n=4x=48) is the most cultivated type of blueberry, both in New Zealand and overseas. Its perceived nutritional value is conferred by phytonutrients, particularly anthocyanins. Identifying the genetic mechanisms that control the biosynthesis of these metabolites would enable faster development of cultivars with improved fruit qualities. Here, we used recently released tools for genetic mapping in autotetraploids to build a high-density linkage map in highbush blueberry and to detect quantitative trait loci (QTLs) for fruit anthocyanin content. Genotyping was performed by target sequencing, with ~18,000 single nucleotide polymorphism (SNP) markers being mapped into 12 phased linkage groups (LGs). Fruits were harvested when ripe for two seasons and analyzed with high-performance liquid chromatography-mass spectrometry (HPLC-MS): 25 different anthocyanin compounds were identified and quantified. Two major QTLs that were stable across years were discovered, one on LG2 and one on LG4, and the underlying candidate genes were identified. Interestingly, the presence of anthocyanins containing acylated sugars appeared to be under strong genetic control. Information gained in this study will enable the design of molecular markers for marker-assisted selection and will help build a better understanding of the genetic control of anthocyanin biosynthesis in this crop.